The Effect of Bait on The Catch Composition of Square Folding Trap in Rawa Pening Semarang Regency - Hafiz Cahyo Dwi Nugroho; Mardanang Wismo Aji; Nahla Alfiatunnisa; Suwarman Partosuwiryo; Djumanto Djumanto; Rusmilyansari Rusmilyansari; Eko Setyo Budi (TROPICAL WETLAND JOURNAL, 2020)
This study aims to determine the effect of the type of bait on the composition of the catch fish, catch rate, and trap rate using square folding traps. The study was conducted at three fishing locations in October 2019-January 2020 using the experimental fishing method. The operation of square folding traps was done by a total of 60 units. The types of bait used are golden snails, shrimp paste, and trash fish. Fish catches were recorded in number, type, length, and weight, and analyzed using one-way anova test and kruskal wallis test. The composition of the square folding traps catches consists of six species. Marble goby (Oxyeleotris marmorata) is the most dominant catch (60%). The highest catch rate was obtained from box folding traps which were given golden snail bait at 173.50 g/trip, then trash fish bait at 76.88 g/trip and shrimp paste feed at 59.22 g/trip. The highest trap rate is golden snail bait of 12.33%. The bait treatment gives a real difference to the amount and weight of the catch, the golden snail bait gives the highest total number and weight of the catch compared to other baits.